Association of gene expression with blood metabolites and fatty acid profile in lambs - Lemus , Clemente; Bugarín, Job; Lemus , Gilberto; Rodríguez , Javier; Peña, Gabriela; Loya, José (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
Some agricultural byproducts can be used as viable alternatives in animal feed. Therefore, the effect of the inclusion of avocado meal and sunflower oil on the profile of fatty acids, blood metabolites and the expression of genes associated with lipid metabolism in lambs was evaluated. Three treatments were evaluated: 0 % control, 10 % avocado meal and 10 % sunflower oil for 84 days. It was found that including avocado meal in the diet increased the amount of blood glucose and also globulin, but decreased creatinine and Glutamic Oxaloacetic Transaminase, compared to the addition of sunflower oil where the content of cholesterol, triglycerides, and VLDL decreased. and R A/G. There was no difference for muscle fat percentage. The concentration of fatty acids C20:0, C20:1 and C23:0 was lower with avocado meal, without affecting the MUFA and UFA values, the UFA/SFA ratio and the saturation index. The inclusion of avocado meal caused a change in the expression of the ACACA, FASN, SCD, FASBP3, PPARG and SREBF1 genes in the Longisimus thoracis muscle, there was a positive association between glucose and the FASBP3 gene, also of HDL with the PPARG gene, MUFA, proteins and indices of desaturation of fatty acids were associated with genes such as SCD, FASN, SREBF1 and ACACA The inclusion of avocado meal is an alternative to modify genetic expression, also to reduce very low density cholesterol values in the blood.